The story of the Umayyad Caliph - Basri, Muhammad; Ain, Dwi Nur Attira; Nabila, Nabila; Wibowo, Salsabila (Lembaga Riset Mutiara Akbar, 2024)
This article presents an in-depth analysis of the history of the founding of the Umayyad dynasty in 661 AD, with a focus on the post-civil war context in the Muslim community. The appointment of Muawiyah bin Abi Sufyan as the first Caliph was the starting point for the shift in power from Khulafaur Rasyidin to the Umayyad family-based dynasty. This aspect of history is explored by paying attention to the key events that shaped this dynasty. The analysis in the journal describes the period of glory and success of the Umayyads under the reign of Caliph Abdul Malik and Al-Walid bin Abdul Malik. The factors that contributed to this success, such as infrastructure development, economic progress, and political stability, are analyzed in detail. The construction of landmarks such as the Umayyad Mosque in Damascus is also a focus in exploring the architectural and cultural achievements of that time. and explore the factors that led to dramatic changes in political and social structures. The analysis involves authoritarian rule, popular resistance, and internal conflict which reached its peak with the Karbala Massacre in 680 AD. An in-depth understanding of these tensions and changes is the core of this subchapter. This paper makes a significant contribution to the understanding of the history of the Umayyad dynasty, presenting a comprehensive view of the events and dynamics that shaped and ended their reign.